2021
DOI: 10.3390/nu13041255
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Intake and Proteinuria/Albuminuria in the Population—Observational, Cross-Sectional Study

Abstract: Sodium effects on proteinuria are debated. This observational, cross-sectional, population-based study investigated relationships to proteinuria and albuminuria of sodium intake assessed as urinary sodium/creatinine ratio (NaCR). In 482 men and 454 women aged 35–94 years from the Moli-sani study, data were collected for the following: urinary NaCR (independent variable); urinary total proteins/creatinine ratio (PCR, mg/g), urinary albumin/creatinine ratio (ACR, mg/g), and urinary non-albumin-proteins/creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For healthy diet, lower sodium intake was related to a lower risk of proteinuria, whereas the other four components and ideal healthy dietary score did not reduce proteinuria in our study. Higher sodium intake was found to be a risk factor for hypertension and was associated with an increased incidence of proteinuria and CKD progression in previous studies [ 44 , 45 ]. The adverse effect of salt intake on the kidneys may be associated with increased blood pressure and RAAS system dysregulation [ 46 ].…”
Section: Discussionmentioning
confidence: 96%
“…For healthy diet, lower sodium intake was related to a lower risk of proteinuria, whereas the other four components and ideal healthy dietary score did not reduce proteinuria in our study. Higher sodium intake was found to be a risk factor for hypertension and was associated with an increased incidence of proteinuria and CKD progression in previous studies [ 44 , 45 ]. The adverse effect of salt intake on the kidneys may be associated with increased blood pressure and RAAS system dysregulation [ 46 ].…”
Section: Discussionmentioning
confidence: 96%
“…As shown in Figure S1 of Supplementary Materials , the stratification was designed to have 100 men and 100 women for each one of the following five age-groups: 35–44, 45–54, 55–64, 65–74, and ≥75 years. The additional data collection in this target cohort included the average local solar irradiance in the month preceding the blood withdrawal as objective index of ultraviolet exposure and the measurements by automated biochemistry of serum calcidiol, serum creatinine, urine albumin, urine total protein, and urine markers of diet as reported [ 18 , 19 ]. Serum calcidiol was measured by a chemiluminescent assay (Diasorin, Saluggia, Italy) calibrated with ID-LC-MS- and ID-LC-MS/MS-traceable standard NIST-SRM 972a as per guidelines [ 7 , 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 24-h urinary albumin excretion rate is regarded as the gold standard for measuring albuminuria. However, most of the literature has adopted the albumin/creatine ratio as an alternative due to convenience and cost 5,6 .The relationships of sodium and potassium with albuminuria have not been fully elucidated, and findings are not consistent in the literature. Several studies 7,8 have shown that sodium intake is positively correlated with urinary albumin.…”
mentioning
confidence: 99%
“…The 24-h urinary albumin excretion rate is regarded as the gold standard for measuring albuminuria. However, most of the literature has adopted the albumin/creatine ratio as an alternative due to convenience and cost 5,6 .…”
mentioning
confidence: 99%